2021
DOI: 10.1186/s12889-021-11458-5
|View full text |Cite
|
Sign up to set email alerts
|

Body image perception and body composition in early adolescents: a longitudinal study of an Italian cohort

Abstract: Background Adolescence is a sensitive period of life in which everyone faces physical and psychological changes. No longitudinal studies considering changes in body image perception and body composition in Italian adolescents have been carried out. The aims of this study were to evaluate the longitudinal change in body composition and weight status in a sample of Italian students of both sexes over the 3 years of middle school and to analyse the influence of these parameters on the perception a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 63 publications
3
23
1
Order By: Relevance
“…Most of our sample was of normal weight, independently from geographical provenience, with few volunteers allocated in the extreme categories of BMI: 8.9% were underweight (11.4% of the Mediterranean volunteers and 6.8% of the non-Mediterranean ones) and 3.8% were obese (all coming from non-Mediterranean countries). The prevalence of volunteers with a normal weight agrees with results from other studies which, however, do not consider the multicultural aspects which have been considered in our study [33,35].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Most of our sample was of normal weight, independently from geographical provenience, with few volunteers allocated in the extreme categories of BMI: 8.9% were underweight (11.4% of the Mediterranean volunteers and 6.8% of the non-Mediterranean ones) and 3.8% were obese (all coming from non-Mediterranean countries). The prevalence of volunteers with a normal weight agrees with results from other studies which, however, do not consider the multicultural aspects which have been considered in our study [33,35].…”
Section: Discussionsupporting
confidence: 91%
“…Adolescence is also considered a critical window for the development of overweight and obesity, and there is consistent evidence showing that excess weight in youth tends to track into adulthood [33]. The aetiology of adolescent overweight and obesity is multifactorial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All the studies were conducted on samples of students except two studies on athletes, two studies on Chinese samples [ 46 , 69 ], that employed a secondary-analyses of data from the China Health and Nutrition Survey (CHNS), and the Indonesian household survey [ 59 ]. The majority of studies had a cross-sectional design, and only three studies had a longitudinal or repeated measures design [ 38 , 42 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies underlined the association between BI and BMI, especially in overweight and obesity categories [ 38 , 41 , 43 , 46 , 57 , 59 , 60 , 63 , 65 , 67 ]. In almost all the studies that reported this association, overweight and obese adolescents had higher body dissatisfaction and less body perception consistency, evaluating themselves as slimmer than they were.…”
Section: Resultsmentioning
confidence: 99%